2011
DOI: 10.1186/1471-244x-11-20
|View full text |Cite
|
Sign up to set email alerts
|

Health status and lifestyle factors as predictors of depression in middle-aged and elderly Japanese adults: a seven-year follow-up of the Komo-Ise cohort study

Abstract: BackgroundDepression is a common mental disorder. Several studies suggest that lifestyle and health status are associated with depression. However, only a few large-scale longitudinal studies have been conducted on this topic.MethodsThe subjects were middle-aged and elderly Japanese adults between the ages of 40 and 69 years. A total of 9,650 respondents completed questionnaires for the baseline survey and participated in the second wave of the survey, which was conducted 7 years later. We excluded those who c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 49 publications
6
69
1
1
Order By: Relevance
“…This study's findings were similar to findings from previous studies [39,44e46]. Gavin et al asserted that if a subject's level of education were low, she would likely experience more depression at the ages of 40e65 years [46]. identified that an adult with a chronic disease was at a higher risk of experiencing depression [45].…”
Section: Discussionsupporting
confidence: 91%
“…This study's findings were similar to findings from previous studies [39,44e46]. Gavin et al asserted that if a subject's level of education were low, she would likely experience more depression at the ages of 40e65 years [46]. identified that an adult with a chronic disease was at a higher risk of experiencing depression [45].…”
Section: Discussionsupporting
confidence: 91%
“…20 To assess fat intake, participants were asked about a conscious effort to avoid foods that are high in fat. Answer categories ranged from never (1) to always (5). Another item assessing fast food consumption was, "How often do you eat at fast food restaurants, drive-ins, or lunch wagons?"…”
Section: Methodsmentioning
confidence: 99%
“…and (4) "How often have you felt difficulties were piling up so high that you could not overcome them?" The response scale ranged from never (0) to very often (5). Items were aggregated in such a way that stress severity ranged from 0 to 20.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, older adults having the physical illness are reported to have higher depression scores (Casey, 2012). Also, physically inactive men were at a greater risk for both healthy aging (Blazer, 2005) and geriatric depression (Tanaka, Sasazawa, Suzuki, Nakazawa, & Koyama, 2011).…”
mentioning
confidence: 99%